2021
DOI: 10.1007/s00418-020-01942-1
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression pattern of calcium-responsive transactivator in early postnatal and adult testes

Abstract: Calcium-responsive transactivator (CREST), a nuclear protein highly expressed in postmitotic neurons, is involved in the regulation of cell cycle, differentiation and dendritic development of neuronal cells. Its mRNA has been detected in the testis of adult rat, whilst its protein expression and distribution pattern in the testis remain to be elucidated. In this study, we examined the distribution of CREST in the adult testes of both rats and human as well as the expression pattern of CREST in the testes of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The SS18L1 protein consists of three functional domains, an N-terminal auto-regulatory domain that suppresses transactivation in the basal state, a central methionine-rich domain involved in protein-protein interaction, and a C-terminal glutamine-rich domain responsible for transactivation ( 13 ). Northern blot, in situ hybridization, immunohistochemistry and Western blotting analysis all showed that the expression of SS18L1 is enriched in the brain ( 14 ). SS18L1 is an essential component of the nBAF neuron-specific chromatin remodeling complex that is related to the chromatin remodeling complex called switch/sucrose non-fermentable (SWI/SNF) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SS18L1 protein consists of three functional domains, an N-terminal auto-regulatory domain that suppresses transactivation in the basal state, a central methionine-rich domain involved in protein-protein interaction, and a C-terminal glutamine-rich domain responsible for transactivation ( 13 ). Northern blot, in situ hybridization, immunohistochemistry and Western blotting analysis all showed that the expression of SS18L1 is enriched in the brain ( 14 ). SS18L1 is an essential component of the nBAF neuron-specific chromatin remodeling complex that is related to the chromatin remodeling complex called switch/sucrose non-fermentable (SWI/SNF) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role for the normal development of the nervous system, such as neuronal growth and differentiation ( 16 ). SS18L1 is involved in cell cycle regulation and differentiation of neurons through switching SWI/SNF by replacing its homologous protein SS18 in the complex ( 14 ). In addition, SS18L1 is shown to bind chromatin remodeling proteins BAF250 and BRG-1, and plays a crucial role in the differentiation and maturation of the spermatogenic epithelial cells ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry staining was performed as previously described [ 44 ]. For immunohistochemical detection of NOL12 and ATR in the retina with the ABC method, the rat eyes were collected, fixed with 4% paraformaldehyde, embedded in paraffin, and serially sectioned at a thickness of 8 µm.…”
Section: Methodsmentioning
confidence: 99%